DETERMINATION OF SLUM AREA STATUS IN SUSTAINABLE DEVELOPMENT PLANNING OF TANJUNGBALAI CITY - Ema Carolin Rotua Pasaribu; Abdi Sugiarto; Cut Nuraini (Bulletin of Engineering Science, Technology and Industry, 2025)
Determination of slum status is an important initial step in sustainable development planning in Tanjungbalai City. This study aims to evaluate the existing conditions of slum areas in the city and analyze the role of slum status determination in supporting sustainable urban development planning. Based on the data collected, slum status determination allows for more targeted planning in infrastructure improvement, fulfillment of basic needs, and community empowerment. However, there are a number of obstacles in this process, including limited accurate data, less than optimal inter-sectoral coordination, and community resistance to change. Therefore, a comprehensive strategy is needed, including strengthening data systems, cross-sectoral coordination, increasing community participation, supportive policies, and sustainable funding to strengthen the slum status determination process and realize sustainable urban development. This study provides recommendations for the Tanjungbalai City government to continue to strengthen collaboration between the government, community, and private sector in order to achieve inclusive and sustainable development goals.